The Costs and Benefits of Mandatory Securities Regulation: Evidence from Market Reactions to the JOBS Act of 2012 - Dhammika Dharmapala; Vikramaditya Khanna (Center for Economic Studies and ifo Institute (CESifo), 2014)
The effect of mandatory securities regulation on firm value has been a longstanding concern across law, economics and finance. In 2012, Congress enacted the Jumpstart Our Business Startups ( JOBS ) Act, relaxing disclosure and compliance obligations for a new category of firms known as emerging growth companies (EGCs) that satisfied certain criteria (such as having less than 1 billion of annual revenue). The JOBS Act's definition of an EGC involved a limited degree of retroactivity, extending its application to firms that conducted initial public offerings (IPOs) between December 8, 2011 and April 5, 2012 (the day the bill became law). The December 8 cutoff date was publicly known prior to the JOBS bill's key legislative events, notably those of March 15, 2012, when Senate consideration began and the Senate Majority Leader expressed strong support for the bill. We analyze market reactions for EGCs that conducted IPOs after the cutoff date, relative to a control group of otherwise similar firms that conducted IPOs in the months preceding the cutoff date. We find positive and statistically significant abnormal returns for EGCs around March 15, relative to the control firms. This suggests that the value to investors of the disclosure and compliance obligations relaxed under the JOBS Act is outweighed by the associated compliance costs. The baseline results imply a positive abnormal return of between 3% and 4%, and the implied increase in firm value is at least 20 million for an EGC with the median market value in our sample.
Keywords: G18; 330; securities regulation; JOBS Act of 2012; emerging growth companies